Specialist physicians' referral behavior regarding preimplantation genetic testing for single-gene disorders: Is there room to grow? - Sarah Capelouto, M.D; Melanie Evans, M.D; Jennifer Shannon, M.D; Katelyn Jetelina, Ph.D., M.P.H; Orhan Bukulmez, M.D; Bruce Carr, M.D (Elsevier, 2021)
Objective: To assess whether primary care specialists' demographics, specialty, and knowledge of preimplantation genetic testing for monogenic disorders (PGT-M) influence their practice patterns. Design: Cross-sectional survey study. Setting: Academic medical center. Patient(s): Not applicable. Intervention(s): None. Main Outcome Measure(s): Objective PGT-M knowledge, subjective comfort with PGT-related topics, PGT care practices (discussions/referrals), and PGT-M implementation barriers. Result(s): Our survey had 145 respondents: 65 obstetrician/gynecologists, 36 internists, and 44 pediatricians. Overall, 88% believed that patients at a risk of passing on genetic disorders should be provided PGT-M information. However, few discussed PGT-M with their patients (24%) or referred them for testing (23%). Over half (63%) believed that the lack of physician knowledge was a barrier to PGT use. In terms of subjective comfort with PGT, only 1 in 5 physicians felt familiar enough with the topic to answer patient questions. There were higher odds of discussing (odds ratio, 3.21; 95% confidence interval, 1.75-5.87) or referring for PGT (odds ratio, 2.52; 95% confidence interval, 1.41-4.51) for each additional 0.5 correct answers to PGT knowledge-related questions. The odds of referring patients for PGT-M were the highest among obstetrician/gynecologists compared with those among the internists and pediatricians. Conclusion(s): Physician specialty and PGT knowledge were associated with PGT-M care delivery practices. Although most specialists believed in equipping at-risk patients with PGT-M information, <1 in 4 discussed or referred patients for PGT. The low levels of PGT-related care among providers may be owed to inadequate knowledge of and comfort with the topic. An opportunity to promote greater understanding of PGT-M among primary care specialists exists and can in turn improve the use of referrals to PGT-M services.